1995
DOI: 10.1111/j.1651-2227.1995.tb13862.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, puberty and obesity after treatment for leukaemia

Abstract: Final height, body proportions, pubertal growth and body mass index were studied retrospectively in 142 survivors of acute lymphoblastic leukaemia (ALL). Treatment consisted of combination chemotherapy and cranial irradiation (18 or 24 Gy). Significant standing height loss and disproportion, with a relatively short back, was seen in both radiation dose groups. Girls were more severely affected than boys. Pubertal growth was adversely affected, with a reduction in peak height velocity in both sexes. Puberty occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 34 publications
2
30
2
2
Order By: Relevance
“…The frequency and pattern of obesity in survivors of ALL is less well documented than the effect of this disease on linear growth. Nevertheless, it is calculated that nearly half of the long-term survivors of childhood leukemia are overweight (25,26). Endocrine disorders causing blunted growth, e.g.…”
Section: Timementioning
confidence: 99%
“…The frequency and pattern of obesity in survivors of ALL is less well documented than the effect of this disease on linear growth. Nevertheless, it is calculated that nearly half of the long-term survivors of childhood leukemia are overweight (25,26). Endocrine disorders causing blunted growth, e.g.…”
Section: Timementioning
confidence: 99%
“…The prevalence of overweight/obesity ranged between 29% to 69% in 14 studies that Age at study and year since Dx are the mean or median as reported or estimated based on the reported age at diagnosis and duration of follow-up (the mean duration of treatment was estimated to be 2.5 y if not indicated by the study). evaluated pediatric ALL survivors off treatment 5 to 9 years (mean/median age = 13.2-19.4 years) [8][9][10]24,33,[51][52][53][54][55][56][57][58] except for 1 early study published in 1986 59 that reported a prevalence of obesity of 8% ( Table 2). The prevalence of overweight/obesity was fairly consistent in 5 studies that evaluated pediatric ALL survivors off treatment $10 years (mean/median age = 20.5-24.1 years), ranging from 34% to 46% 7,14,40,60,61 (Table 3).…”
Section: Prevalence Of Obesity In Pediatric All Survivorsmentioning
confidence: 99%
“…10,11,14,34,47,51,60 However, the other 15 studies did not find evidence of a gender difference. [6][7][8]12,15,28,31,33,36,38,47,[52][53][54]62 FIGURE 2…”
Section: Obesity In Pediatric All Survivors By Patient and Treatment mentioning
confidence: 99%
“…[1][2][3][5][6][7] Conditioning regimen chemotherapy and irradiation are often superimposed on the 'standard' therapies, which may compromise pubertal development and final height (FH) in their own right. 8 Also, with the increasing number of survivors and duration of follow-up, patients may experience a significant loss of height potential. The literature contains a number of studies about factors that adversely affect growth in children treated for AL (age at the time of AL treatment, irradiation dose and fraction size, and so on).…”
Section: Introductionmentioning
confidence: 99%